2014
DOI: 10.1090/s0002-9939-2014-12258-1
|View full text |Cite
|
Sign up to set email alerts
|

Critical points of random polynomials with independent identically distributed roots

Abstract: Abstract. Let X 1 , X 2 , . . . be independent identically distributed random variables with values in C. Denote by µ the probability distribution of X 1 . Consider a random polynomial Pn(z) = (z − X 1 ) . . . (z − Xn). We prove a conjecture of Pemantle and Rivin [arXiv:1109.5975] that the empirical measure µn := 1 n−1 P ′ n (z)=0 δz counting the complex zeros of the derivative P ′ n converges in probability to µ, as n → ∞.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 9 publications
2
56
0
Order By: Relevance
“…The assumption on µ being compactly supported is clearly not sharp, our proof immediately transfers to probability measures having a certain rate of decay at infinity. The result is similar in spirit to a recent result of Kabluchko [9] (proving a conjecture of Pemantle & Rivin [11]) who showed that the distribution of critical points {z ∈ C : p n (z) = 0} reproduces µ for general probability measures µ. If µ is not radial, the situation is not quite as simple.…”
Section: Introduction and Main Resultssupporting
confidence: 86%
“…The assumption on µ being compactly supported is clearly not sharp, our proof immediately transfers to probability measures having a certain rate of decay at infinity. The result is similar in spirit to a recent result of Kabluchko [9] (proving a conjecture of Pemantle & Rivin [11]) who showed that the distribution of critical points {z ∈ C : p n (z) = 0} reproduces µ for general probability measures µ. If µ is not radial, the situation is not quite as simple.…”
Section: Introduction and Main Resultssupporting
confidence: 86%
“…To conclude, let us mention the works of Kabluchko [10], Pemantle-Rivlin [13], and Subramanian [16], which study the empirical measure of critical points for ensembles of random polynomials similar to the ones we consider here. We also point the reader to the work of Nazarov-Sodin-Volberg [12] and the recent article of Feng [6], which both concern the critical points of random holomorphic functions with respect to a smooth connection.…”
Section: Sendov's Conjecturementioning
confidence: 99%
“…The proofs here are adapted from the proof of Kabluchko's theorem as presented in [5]. The proofs involve in analyzing the function L n (z) := P n (z) Pn(z) = n k=1 1 z−ξ k .…”
Section: Outline Of Proofsmentioning
confidence: 99%